Eksistensi identitas nasional indonesia dalam menghadapi tantangan globalisasi - nurlaila, acha (Maliki Interdisciplinary Journal, 2026)
National identity is the identity of a nation that reflects the values, culture, language, and ideology possessed by a country. In the era of globalization, the rapid development of technology and information has greatly influenced the lives of Indonesian people, especially the younger generation. The unrestricted entry of foreign cultures may cause a decline in nationalism and understanding of national values. This article aims to discuss the existence of Indonesian national identity in facing the challenges of globalization and the efforts that can be made to preserve it. The method used in this article is a literature study by examining various sources such as books, journals, and scientific articles. The results show that national identity can be maintained through strengthening character education, preserving local culture, implementing Pancasila values, and increasing patriotism within society. Therefore, national identity must continue to be preserved so that the Indonesian nation does not lose its identity amid the development of modern globalization.